2009
DOI: 10.1158/0008-5472.can-08-4967
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Competing Endocytic Pathways for Overcoming the Tumor-Blood Barrier: Magnetic Resonance Imaging and Near-Infrared Imaging of Bifunctional Contrast Media

Abstract: Ovarian cancer is the most lethal gynecologic malignancy, often diagnosed at advanced stage leading to poor prognosis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
3
12
0
Order By: Relevance
“…Suppression of caveola-mediated internalization by nystatin remarkably increases the uptake of such contrast media by tumor cells. 14 Recently, Ishida et al 15 reported that a copper chelator enhances the uptake and the therapeutic efficacy of cisplatin in cancerous tissues via attenuating the competing effect of copper on cisplatin uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of caveola-mediated internalization by nystatin remarkably increases the uptake of such contrast media by tumor cells. 14 Recently, Ishida et al 15 reported that a copper chelator enhances the uptake and the therapeutic efficacy of cisplatin in cancerous tissues via attenuating the competing effect of copper on cisplatin uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Further modification of the contrast media such as generation of bifunctional daidzein-BSA-GdDTPA, led to enhanced delivery and retention by the tumor cells, across the perivascular stroma myofibroblasts [19]. …”
Section: Imaging Interstitial Convection and Lymphatic Drainmentioning
confidence: 99%
“…In addition, albumin can be further modified so as to include fluorescent or NIR tags (Fig. 2a) or additional targeting moieties [16, 19] widening the possible in vitro and in vivo follow up methods.…”
Section: Introductionmentioning
confidence: 99%
“…Our above mentioned studies with targeted alliinase conjugates suggested that a similar targeted strategy could be used against ovarian cancer cells which are known to express recognition sites for the isoflavone daidzein (Migalovich et al, 2009). The main goal of the present study was to develop a daidzein-alliinase conjugate and to assess its ability to target ovarian cancer cells and to effectively produce in vivo, cytotoxic allicin molecules in an animal model of ovarian cancer.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, daidzein appears to act as a weak estrogen, it recognizes a putative plasma membrane estrogen receptor (Somjen et al, 2005), a membrane located ERβ-related protein (de Wilde et al, 2006) or a nuclear estrogen receptor of the β-type (Kuiper et al, 1998). In a previous study we have shown that conjugation of daidzein to bovine serum albumin labeled with the fluorescent probe CyTE-777, enabled the specific delivery of the probe to the ovarian cancer cells (Migalovich et al, 2009). Furthermore a chemical conjugate between daidzein and the anticancer drug daunomycin was shown to be more effective and less toxic at low concentrations, than daunomycin alone in killing the MLS human ovarian cancer cells (Somjen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%